Connecting Saving and Food Security: Evidence from an Asset‐Building Program for Families in Poverty. Issue 3 (16th December 2016) - Loibl, Cäzilia; Snyder, Anastasia; Mountain, Travis
Abstract : This study examines food insecurity among children of participants in a federally funded savings program in the United States, the Individual Development Account (IDA) program. We measure child food insecurity of savings program families by using the eight questions of the Current Population Survey's Food Security Supplement. About 39.4% of savings program families report food insecurity. No differences in children's food hardship between current and past program participants were identified. Examining predictors, propensity to plan for money tend to be associated with higher odds of children's food insecurity. By contrast, frugal behavior, lower material deprivation, and higher subjective well‐being tend to reduce the odds of children's food insecurity. Findings also confirm previous literature on the association of alternative financial services and higher food insecurity among children.